2008
DOI: 10.1021/jo802040q
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of N-Methyl and N-Phenyl meso-Unsubstituted N-Confused Porphyrins

Abstract: Condensations of 1-methyl and 1-phenyl-2,4-pyrroledicarbaldehydes with a tripyrrane in TFA-dichloromethane, followed by oxidation with aqueous FeCl(3), gave novel cross-conjugated meso-unsubstituted N-confused porphyrins (NCPs; 12). These porphyrin analogues showed significant diatropic ring currents that were enhanced upon protonation. Reactions with nickel(II) acetate in refluxing DMF, or palladium(II) acetate in acetonitrile, gave good yields of the corresponding nickel(II) or palladium(II) organometallic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 69 publications
1
44
0
Order By: Relevance
“…It has been shown that the inner carbon may be a target for protonation. [24,38] However, protonation does not secure the configuration stability of C21, which reversibly adopts a pyramidal hybridization of the cation [2ÀH] + , so the enantiomers cannot be separated. On the other hand, in the reaction with haloalkanes a new C À C bond is formed between the coordinated C21 and a carbocation derived from R À X.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the inner carbon may be a target for protonation. [24,38] However, protonation does not secure the configuration stability of C21, which reversibly adopts a pyramidal hybridization of the cation [2ÀH] + , so the enantiomers cannot be separated. On the other hand, in the reaction with haloalkanes a new C À C bond is formed between the coordinated C21 and a carbocation derived from R À X.…”
Section: Resultsmentioning
confidence: 99%
“…23,24 During investigations into the synthesis of 2-substituted NCPs 15 by this approach (Scheme 3), it was noted that silver(I) acetate could be used to oxidize the initially formed N-confused phlorin 16 to give a lactam-type derivative 17. 24 In addition, pyrazolecontaining phlorins 18 were similarly shown to be oxidized to the corresponding oxophlorins 19 in the presence of silver(I) acetate (Scheme 3). 25 Based on these observations, we speculated that this methodology could be used to obtain superior yields of oxopyriphlorins 6 (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
“…[46a] N-Methyl and N-phenyl NCPs 25 have also been prepared, and these readily formed the corresponding Ni II and Pd II complexes 26 and 27 (Scheme 8). [25] Addition of TFA to solutions of these metallo-derivatives also gave aromatic C-protonated species 26H + and 27H + , respectively. A higher concentration of TFA was required to form the protonated palladium complexes 27H + compared to the nickel species 26H + , but the palladium complexes proved to be far more stable under acidic conditions.…”
Section: Synthesis Of Carbaporphyrinoid Systemsmentioning
confidence: 97%
“…NCP 25 a also reacted with goldA C H T U N G T R E N N U N G (III) acetate to give a low yield of the related goldA C H T U N G T R E N N U N G (III) complex 29. [25] The metalated derivatives demonstrate modified reactivity that enables the synthesis of substituted NCPs. For instance, silverA C H T U N G T R E N N U N G (III) NCP 17 reacted with dimethylamine to give the 21-dimethylamino-NCP 30, [55] while reaction with potassium diphenylphosphide afforded the 21-diphenylphosphanyl-NCP 31 (Scheme 9).…”
Section: Synthesis Of Carbaporphyrinoid Systemsmentioning
confidence: 99%